Resolving the porosity-unmelted inclusion dilemma during in-situ alloying of Ti₃₄Nb via laser powder bed fusion - Huang, Sheng (2021)
A parametric experimental study on the role played by the power (P), velocity (VL) and profile (top-hat or Gaussian) of the laser on the porosity, inclusion content and microstructural evolution of in-situ alloyed laser powder bed fusion (LPBF) manufactured Ti34Nb was conducted. For this, alloys were printed with three sets of processing parameters, in which the above-mentioned parameters were varied but the energy density was held constant. A detailed tomographic and microstructural investigation of these alloys was followed by tensile tests. Observations of melt pools in the single tracks and single stripes were complemented by thermal finite element method (FEM) simulations that studied their evolution. Results show that a top-hat laser profile combined with high P (> 650 W), high VL (> 650 mm/s) and short stripe width scanning strategy forms a large single stripe melt pool that moves slowly and has a low aspect ratio. The large and slow melt pool allows Nb to melt efficiently and minimizes its unmelted content while the low melt pool aspect ratio prevents keyholing that can otherwise result in porosity. These melt pool attributes also favor the formation of a columnar β-Ti microstructure with a strong {100} texture, which has the ideal combination of strength and elastic modulus. The mechanisms of microstructural evolution were explained and the scope of this parameter optimization principle was discussed in the context of further improving the properties of this alloy.